Politics Across the Hudson : The Tappan Zee Megaproject - Plotch, Philip Mark, 1961- (Book collections on Project MUSE., 2015)
"A behind-the-scenes look at three decades of planning and politics for the new Tappan Zee Bridge reveals essential lessons for those interested in tackling complex public policy problems, yet it will also confirm your worst fears about governmental dysfunction. The New York metropolitan area abandoned viable options, squandered hundreds of millions of dollars, forfeited more than three billion dollars in federal funds, and missed out on important opportunities. For more than 30 years, New York officials were unable to develop a consensus on a realistic plan to improve transportation conditions in New York's northern suburbs. Planning improvements for a region with more than 22 million people is difficult enough, but several state officials made it even harder when they raised false expectations about government's ability to solve a problem. Three governors preferred to keep studying various alternatives rather than disappointing key constituencies. Faced with the public's unrealistic expectations, it seemed impossible to identify a solution that was both practical and popular. The governors had little to gain from lowering expectations; instead they were trapped by them. One troubling lesson from the I-287 / Tappan Zee Bridge planning process is that leaders who expedite projects often do so by making decisions behind closed doors with little community input. Although everyone supports government transparency and public participation, in reality too much public involvement gets in the way of finalizing plans and constructing megaprojects"--